Elastic Stable Intramedullary Nailing and Temporary External Fixation for the Treatment of Unstable Femoral Shaft Fractures in Children Aged 5-11 Years Old: A Retrospective Study of 28 Cases - Lu, Yunan; Canavese, Federico; Lin, Ran; Chen, Jinchen; Chen, Yibin; Huang, Yuling; Chen, Shunyou (Frontiers in Pediatrics, 2022)
Purpose Unstable femoral shaft fractures (UFSFs) in children aged 5-11 years remain challenging due to their intrinsic instability. The aim of this study was to evaluate the clinical and radiographic outcomes of UFSF in children aged 5 to 11 years managed by the combined use of ESIN and temporary EF. Methods Children with UFSF (long oblique and comminuted) treated by ESIN and temporary EF were retrospectively reviewed. Sex, age at injury, side involved, type of fracture, presence or absence of associated lesions or neurovascular complications, type of treatment, time from trauma to surgery, duration of surgery, radiation exposure and length of postoperative immobilization were collected from the medical charts. Radiological and functional outcomes were evaluated according to Beaty’s and Flynn’s criteria, respectively. Results A total of 28 consecutive patients with closed or open (Gustilo type I or II) UFSF were reviewed (18 boys and 10 girls). The mean age at injury was 8.7 ± 1.6 years (range, 5-11); the average weight was 38.1 ± 7.6 kg (range, 26-55). The mean hospital stay was 3.7 ± 1.4 days (range, 2–7), and the mean time to EF and ESIN removal was 6.5 ± 1.1 weeks (range, 4–8) and 9.4 ± 1.6 months (range, 6–12), respectively. Twenty-seven out of 28 patients had excellent radiographic outcomes according to Beaty’s criteria, and 24/28 had excellent functional outcomes according to Flynn’s criteria. Overall, 4 complications (14.3%) were recorded. No statistically significant correlation was found between complication rates and sex, age, weight or fracture characteristics (P < 0.05). Conclusions The combined use of ESIN and temporary EF provides good clinical and radiological outcomes in children with UFSF aged between 5 and 11 years, with a reduced complication rate.